Stakeholder theory in social entrepreneurship: a descriptive case study - Ruben Burga; Davar Rezania (Journal of Global Entrepreneurship Research, 2016)
In this paper, a descriptive case study of a social entrepreneurial firm is used to demonstrate stakeholder salience and stakeholder social issue management valence. The methodology is to use a semi structured interview with a social entrepreneur to identify and map the firm's stakeholders' salience and stakeholders' social issue management valence. The resulting map uses spheres, sized proportionally to social issue management valence, to represent the various stakeholder groups. Each map shows the positioning of stakeholders according to their salience at critical points in the life of the social entrepreneurship. This paper contributes to stakeholder theory through its use of an innovative methodology to combine and view the stakeholders and their importance to the social entrepreneur on a single map. This map incorporates the elements of stakeholder salience with stakeholder social issue management valence. This mapping approach enables us to visualize how salience and valence positions change at critical times. Social entrepreneurs applying this mapping method can balance the allocation of their time and attention to stakeholders while simultaneously keeping with their social mission.
Keywords: 650; Social entrepreneurship; Stakeholder theory; Descriptive case study; Stakeholder salience; Social issue management valence